Ethics and digital maximalism: Requirement for critical thinking about technologies - Hernández-Pérez, Tony (Anuario ThinkEPI, 2018)
Information technologies have changed our lives, this includes new ways to generate, collect, and process large volumes of information. Big data are in the hands of large companies that delegate the management of data to algorithms and artificial intelligence programs that play a part in deciding who is the most suitable candidate for a job or who should receive mortgage credit. All this generates new ethical dilemmas; therefore, the existence of digital humanists becomes increasingly necessary. Philosophers, historians, and thinkers with knowledge and a critical vision of technology become the ones who alert and help us understand the limits and consequences of the use of big data.